Distal Metaphyseal Osteotomy Allows for Greater Ulnar Shortening Compared to Diaphyseal Osteotomy for Ulnar Impaction Syndrome: A Biomechanical Study - Luo, T. David; De Gregorio, Michael; Zuskov, Andrey; Khalil, Mario; Li, Zhongyu; Nuñez, Fiesky A., Sr; Nuñez, Fiesky A., Jr (Journal of Wrist Surgery, 2020)
Purpose To compare the biomechanical characteristics between diaphyseal and metaphyseal ulnar-shortening osteotomy with respect to (1) maximal shortening achieved at each osteotomy site and (2) force required to achieve shortening at each site.Methods Nine fresh frozen cadaveric upper extremities were affixed through the proximal ulna to a wooden surgical board. A metaphyseal 20-mm bone wedge was resected from the distal ulna and sequential shortening was performed. A load cell was attached to a distal post that was clamped to the surgical board and used to measure the force required for each sequential 5-mm of shortening until maximal shortening was achieved. The resected bone was reinserted, and plate fixation was used to restore normal anatomy. A 20-mm diaphyseal osteotomy was performed, and force measurements were recorded in the same manner with (1) interosseous membrane intact, (2) central band released, and (3) extensive interosseous membrane and muscular attachments released.Results Metaphyseal osteotomy allowed greater maximal shortening than diaphyseal osteotomy with the interosseous membrane intact and with central band release but similar shortening when extensive interosseous membrane and muscle release was performed. Force at maximal shortening was similar between metaphyseal and diaphyseal osteotomy. Sequential soft tissue release at the diaphysis allowed for increased shortening with slightly decreased shortening force with sequential release.Conclusion Metaphyseal ulnar osteotomy allows greater maximal shortening but requires similar force compared with diaphyseal osteotomy. Sequential release of the interosseous membrane permits increased shortening at the diaphysis but requires extensive soft tissue release.Clinical Relevance Both sites of osteotomy can achieve sufficient shortening to decompress the ulnocarpal joint for most cases of ulnar impaction syndrome. The greater shortening from metaphyseal ulnar osteotomy may be reserved for severe cases of shortening, especially after distal radius malunion or in the setting of distal radius growth arrest in the pediatric population.Level of Evidence This is a Level V, basic science study.
Keywords: cadaver; diaphyseal osteotomy; metaphyseal osteotomy; ulnar impaction syndrome; ulnar-shortening osteotomy